2013
DOI: 10.4236/ape.2013.32011
|View full text |Cite
|
Sign up to set email alerts
|

Time of Day Effect on Soccer—Specific Field Tests in Tunisian Boy Players

Abstract: The purpose of this study was to investigate the diurnal variation in some specific skills performance during field testing in boy's footballer. In a balanced and randomized study design, 15 boys (mean ± SD; age 12.7 ± 1.1 years; height 1.54 ± 9.1 m; body mass 45.1 ± 3.2 kg) participated in the study. Subjects performed some specific soccer skills (kicking accuracy, ball control with the body, ball control with the head, coordination test, zigzag running (i.e., agility), zigzag with the Ball (i.e., dribbling) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
(58 reference statements)
3
13
0
Order By: Relevance
“…The present results are in agreement with those of Gharbi et al (2013) for agility in children, with better performance in the afternoon than the morning. Likewise, Souissi et al (2010Souissi et al ( , 2012 reported that physical performance in children is time-of-day dependent.…”
Section: Downloaded By [University Of Otago] At 09:56 29 July 2015supporting
confidence: 95%
See 3 more Smart Citations
“…The present results are in agreement with those of Gharbi et al (2013) for agility in children, with better performance in the afternoon than the morning. Likewise, Souissi et al (2010Souissi et al ( , 2012 reported that physical performance in children is time-of-day dependent.…”
Section: Downloaded By [University Of Otago] At 09:56 29 July 2015supporting
confidence: 95%
“…In adults soccer players, previous studies reported that peak and mean power during repeated and continuous maximal cycling test ), maximal voluntary contraction (Aloui et al 2013), flexibility, hand-grip strength (Reilly et al 2007), total distance and maximal aerobic velocity during the Yo-Yo test were generally best at the end of the afternoon. In soccer players aged 9 to 12 years, this diurnal variation was confirmed for the agility (Gharbi et al 2013) and the lower limbs strength and power ). However, these tests are not specific to the child activities and to soccer.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…In turn, the diurnal fluctuations in jumping performance we observed were similar to those reported in soccer players (11% improvement in evening hours) ( Reilly et al, 2007 ) and college students (7-10% improvement in evening hours) ( Chtourou et al, 2012 ). Although, the exact underlying mechanisms are still unknown, this temporal change in jump performance could be explained by fluctuations in core temperature, peaking in the late afternoon ( Gharbi et al, 2013 ; Mhenni et al, 2017 ). Indeed, previous authors hypothesised ( Bernard et al, 1997 ; Chtourou et al, 2013b ) concomitant rises in core temperature and gains in short-term maximal performances were causally related.…”
Section: Discussionmentioning
confidence: 99%